2010
DOI: 10.1161/atvbaha.109.198614
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Killer T Cells Are Involved in Adipose Tissues Inflammation and Glucose Intolerance in Diet-Induced Obese Mice

Abstract: Background-Macrophage and lymphocyte infiltration in adipose tissue may contribute to the pathogenesis of obesity-mediated metabolic disorders. Natural killer T (NKT) cells, which integrate proinflammatory cytokines, have been demonstrated in the atherosclerotic lesions and in visceral adipose tissue. Objective-To determine whether NKT cells are involved in glucose intolerance and adipose tissue inflammation in diet-induced obese mice. Methods and Results-To determine whether NKT cells are involved in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
158
4
4

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 32 publications
(35 reference statements)
4
158
4
4
Order By: Relevance
“…NKT cells react to lipid antigens presented on CD1d, which results in the secretion of various cytokines (IL-4, IL-10, IFN-g, and TNF-a) that may elicit Th1, Th2, and Treg responses. Experiments with mice with loss-and gain-offunction in NKT activity revealed a gamut of outcomes ranging from beneficial (21)(22)(23)(24)(25), to null (26), to detrimental (27)(28)(29) effects of NKT cells on metabolism. These divergent effects may result from the various strategies applied (CD1d 2/2 that affects all NKT cells vs. Ja18 2/2 that affects only type 1 NKT cells), various diets, various durations, or other local, yet not identified factors.…”
Section: Immune Cells Orchestrate the Outcome Of At Inflammationmentioning
confidence: 99%
“…NKT cells react to lipid antigens presented on CD1d, which results in the secretion of various cytokines (IL-4, IL-10, IFN-g, and TNF-a) that may elicit Th1, Th2, and Treg responses. Experiments with mice with loss-and gain-offunction in NKT activity revealed a gamut of outcomes ranging from beneficial (21)(22)(23)(24)(25), to null (26), to detrimental (27)(28)(29) effects of NKT cells on metabolism. These divergent effects may result from the various strategies applied (CD1d 2/2 that affects all NKT cells vs. Ja18 2/2 that affects only type 1 NKT cells), various diets, various durations, or other local, yet not identified factors.…”
Section: Immune Cells Orchestrate the Outcome Of At Inflammationmentioning
confidence: 99%
“…Specific NKT cell receptors interact with CD1d-related lipid and glycolipid antigens, thus providing a potential link between obesity, autoimmunity and inflammatory diseases [63,64]. NKT cells could contribute to the development of visceral WAT inflammation during obesity, since HFD-fed NKT-deficient mice (β 2 -microglobulin knockout mice) show lower macrophage accumulation and better glucose tolerance than control mice, with no differences in body weights [65]. However, it has recently been demonstrated that the aforementioned effects of NKT cell deletion on metabolism can only occur in the absence of CD8 + T cells [66].…”
Section: Regulatory T Cellsmentioning
confidence: 99%
“…Indeed, we have shown that iNKT cells activate vascular wall inflammation in atherogenesis and adipose tissue inflammation in obesity-induced glucose intolerance. 7,8 On the other hand, iNKT cells play a protective role against autoimmune and inflammatory diseases such as type 1 diabetes, 9,10 allergic encephalomyelitis, 9,11 and rheumatoid arthritis. 12 These findings suggest that iNKT cells may have bidirectional effects on tissue inflammation.…”
mentioning
confidence: 99%